2016
DOI: 10.2147/ijn.s101741
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of magnetic hyperthermia and in vivo histocompatibility for human-like collagen protein-coated magnetic nanoparticles

Abstract: Magnetic hyperthermia is a promising technique for the minimally invasive elimination of solid tumors. In this study, uniform magnetite nanoparticles (MNPs) with different particle sizes were used as a model system to investigate the size and surface effects of human-like collagen protein-coated MNPs (HLC-MNPs) on specific absorption rate and biocompatibility. It was found that these HLC-MNPs possess rapid heating capacity upon alternating magnetic field exposure compared to that of MNPs without HLC coating, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…These results indicated that PTT combined with VER-M had less recurrence rate than hyperthermia. This results because heatstroke not only directly induces cell injury, but also causes the release of large amounts of inflammatory mediators and cells with extensive biological activities to induce a systemic inflammatory response and immune dysfunction, which has been widely studied 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 . The biocompatibility of the formulation was reflected by the weight change during the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that PTT combined with VER-M had less recurrence rate than hyperthermia. This results because heatstroke not only directly induces cell injury, but also causes the release of large amounts of inflammatory mediators and cells with extensive biological activities to induce a systemic inflammatory response and immune dysfunction, which has been widely studied 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 . The biocompatibility of the formulation was reflected by the weight change during the treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates show that the Zeeman energy μ 0 M s v p H of a magnetite particle with diameter d ∼ 20 nm exceeds the thermal energy kT o if the field H is more than 2 kA m −1 . The typical strength of the magnetic fields used in medical applications lies in the range 2-15 kA m −1 (see, for example, [17,23]). Thus, for the particles with diameter d ≥ 20 nm, in the first approximation, one can neglect the thermal fluctuations of the direction of the particle magnetic moment.…”
Section: Single Particlementioning
confidence: 99%
“…First, because they are not toxic; secondly, they are relatively cheap; and, next, they have magnetic moments sufficient to provide a link with the magnetic fields easily achievable in the laboratory and clinical conditions. It was concluded in [17][18][19] that particles with a diameter in the range 25-30 nm are most efficient for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The typical range of the field, used in the biomedical applications of magnetic hyperthermia, is 2-15 kA m −1 (e.g. [6,10]). Thus, in our analysis we can ignore the fluctuations of the moments' orientations.…”
Section: Physical Model and The Main Simplificationsmentioning
confidence: 99%
“…Therefore, during the heating process, the particle moment is transferred across the potential barrier many times and the models, based on the concept of the Neel remagnetization, are quite adequate to meet the physical reality. However, it was shown in experiments [6][7][8] that the particles with diameters of 25-30 nm are the most efficient for magnetic hyperthermia. For these particles, the time of the Neel relaxation is in the range 2.7 × 10 3 − 3 × 10 12 s. Thus, the probability that the particle transfers the potential barrier for half an hour is very low and the concept of the Neel remagnetization, as the main mechanism of the heat production, is not adequate for the physical process.…”
Section: Introductionmentioning
confidence: 99%